2019
DOI: 10.1055/s-0039-1691486
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Induced Thiocyanation of Enaminones: Synthesis of Functionalized Alkenes and Chromones

Abstract: A simple and efficient electrochemically induced thiocyanation of enaminones under undivided electrolytic conditions has been developed. With this protocol, various polyfunctionalized alkenes and chromones could be obtained in good to excellent yields using readily available KSCN as the thiocyanation reagent under catalyst-, oxidant-, and transition-metal-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 5 publications
(4 reference statements)
0
20
0
Order By: Relevance
“…Zeng, [6b] Xu, [6c] Mei, [6d] and other groups [6e–k] also did related works, respectively. In 2019, Zan Yang et al reported electrochemically induced thiocyanation of enaminones [6l] . As part of our continuing study on electrosynthesis, herein, we report an efficient and facile method to construct alkenyl sulfur compounds by electrochemical anodic oxidation method.…”
Section: Methodsmentioning
confidence: 89%
“…Zeng, [6b] Xu, [6c] Mei, [6d] and other groups [6e–k] also did related works, respectively. In 2019, Zan Yang et al reported electrochemically induced thiocyanation of enaminones [6l] . As part of our continuing study on electrosynthesis, herein, we report an efficient and facile method to construct alkenyl sulfur compounds by electrochemical anodic oxidation method.…”
Section: Methodsmentioning
confidence: 89%
“…Enaminones, an important class of readily available and inexpensive precursors, have been used as valuable synthetic building blocks and found broad applications in various organic and medicinal syntheses . On the other hand, elemental sulfur as the [S] source for the synthesis of sulfur-containing organic compounds has attracted considerable interest .…”
Section: Introductionmentioning
confidence: 86%
“…8 Interestingly, when Ru(bpy) 3 Cl 2 •6H 2 O was employed as the photoredox catalyst, the -thiocyanation reaction provided NH 2 -functionalized thiocyanated enamines through a further amino-exchange process. Shortly afterwards, Zhou and co-workers disclosed a similar -thiocyanation of N,N-dimethyl enaminones in the presence of KSCN using an undivided cell under electrolytic conditions 9 or with PhI(OAc) 2 as an oxidant, 10 respectively. These -thiocyanation reactions were proved to occur via a free-radical pathway.…”
Section: Scheme 6 Direct C(sp 2 )-H -Thiocyanationsmentioning
confidence: 98%
“…In 2019, Zhou and co-workers reported the synthesis of 3-thiocyanyl chromones via both electrochemistry-induced thiocyanation of N,N-dimethyl enaminones using an undivided electrolytic cell and PIDA-mediated thiocyanation of enaminones in water at room temperature (Scheme 62). 9,10 Nevertheless, these two reaction processes involved the addition of a thiocyanyl free radical to the enaminone under the different oxidative conditions. Furthermore, various thiocyanyl chromones could be obtained in good to excellent yields with diverse functional groups using these protocols.…”
Section: Synthesis Of Functionalized Chromonesmentioning
confidence: 99%